Studying the Variations of Complex Electrical Bio-Impedance of Plant Tissues During Boiling. (2016) - Bera, Tushar Kanti; Bera, Sampa; Kar, Kalyan; Mondal, Shubha
Abstract: Biological tissues show complex bioelectrical impedance which depends on the tissue compositions, tissue structure, tissue health and signal frequency. As the tissue composition, structure and health are significantly changed during boiling, there will be a significant change in tissue electrical properties in the boiled tissues. Therefore, impedance variation with tissue boiling can be correlated with the tissue health status and it can be suitably used for noninvasive assessment of tissue health either in food technology or in the medical treatment of a burnt patient. In this direction the impedance variation in banana stem tissues is studied in unboiled and boiled conditions and the responses of the complex bio-impedance are analyzed over a wide range of frequencies. Results demonstrate that the bioelectrical impedance of the plants tissues drastically reduce due to the boiling effect and the α-dispersion and β-dispersion in the bioimpedance found for unboiled tissue disappears in the boiled condition.